Evaluasi Tingkat Kepuasan Pengguna Terhadap SPADA di Universitas Dayanu Ikhsanuddin Berdasarkan Dimensi End User Computing Satisfaction (EUCS) - Musadat, Fithriah; Asniati, Asniati; Yusrianti, Yusrianti (JURNAL INFORMATIKA, 2025)
This study aims to evaluate user satisfaction with the Dayanu Ikhsanuddin University Online Learning System (SPADA Unidayan) based on the five dimensions of the End User Computing Satisfaction (EUCS) model: content, accuracy, format, ease of use, and timeliness. A descriptive statistical approach was employed. Data was collected through questionnaires administered to all students who used SPADA during the Odd Semester of the 2024/2025 Academic Year, totaling 300 respondents. All instrument items were validated using Pearson correlation and tested for reliability using Cronbach’s Alpha, yielding a very high reliability score (α = 0.895). The analysis results indicate that, in general, students perceive SPADA Unidayan as satisfactory, with the majority giving positive responses across all EUCS indicators. User satisfaction and user friendliness received the highest scores. However, neutral and negative responses concerning timeliness and visual design suggest the need for improvements to enhance the overall online learning experience.